Introduction to emergency management - Haddow, George D. (Butterworth Heinemann, 2011)
"Learn about the discipline of emergency management as it has developed over the past six decades, including the rapid evolution of the field since the turn of the century. Haddow, Bullock, and Coppola bring the ideal combination of practical and academic experience to their presentation of disaster preparedness, mitigation, response, recovery and communications. Extensive case studies cover the latest disasters, offering ample opportunity for current students and practitioners to build their critical thinking skills and grow into the next generation of leaders in this increasingly important profession."--Back cover of book.